PERENCANAAN PIPA TRANSMISI SUMBER AIR BAKU SUNGAI BEKUAN BAGI PENDUDUK KECAMATAN LEMBAH BAWANG - Nizar, Sy. Khairul; Yulianto, Eko; ., Umar (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
Analysis begins with the planning phase to determine the water quality of the design of water treatment, after the calculation of flood discharge analysis, followed by analysis of population projections for the next 20 years. After Knowing Population, conducted a needs assessment of the community water valley onions and quantity of water which is owned by River raw water source clot. Recently tested the reliability of the source of raw water for then all the data is processed using Epanet Program. Of Air Quality Test Results in laboratory Health Office dr. Sudarso, Pontianak meragun sirin known that water is still very clean and does not require water treatment. Followed by Analysis Debit Flood Plan using HSS method Snyder is known that the maximum discharge clot River Water Source for the return period of 20 years is 8.7602 liters / sec while the clean water needs at peak hours of 12.7752 liters / sec. Furthermore, from the analysis of the pipeline which will be used using 2.0 Epanet program planned transmission network using HDPE pipe with pipe diameter Ã˜ 150 mm with a distance of 3283 mm.